Waste Material Recycling in the Circular Economy Challenges and Developments - Achilias, Dimitris S. (IntechOpen, 2022)
This book highlights current challenges and developments in waste material recycling in the framework of a circular economy. The increase in the standard of living has resulted in the large consumption of several materials, mainly polymers. Therefore the problem of waste recycling, specifically polymer recycling, in an environmentally friendly way is more urgent than ever. Nowadays, more specialized recycling methods are required to manage a wide variety of wastes. Over fourteen chapters in three sections, this book addresses such topics as chemical recycling techniques, recycling of polyethylene, denim production and recycling, valorization of waste materials, urban mining, the circular economy, and much more.